Pembentukan Karakter Peserta Didik di Lingkungan Pendidikan - Muhammad Al Fatih (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2016)
Character is currently being extremely crowded into the discussion and research for the observer, as well as educational practitioners in Indonesia. Problems began to loss of national character is expressed as the impact of stuttering technology and social patterns. The importance of clear concepts and theories and comprehensively to the character of the nation, should start early generations of children of the nation. This character should be a concern of people everywhere, both in the community that have been developed, and the community is still growing. Because the damage to the character is associated with the mindset, attitudes, and human behavior. If a lot of people who damaged public character, then the impact can harm others. In this context, the deterioration of our nation could be caused by deterioration of the character of the individuals in it. Therefore, the religious teachings containing a high character values ​​that govern the lives of Muslims and is a way of life in all its actions. If the behavior is shown in accordance with the norms in force, such behavior is considered good and acceptable. Character or ethical conduct (ethics) is identical to the action that is based on religion. Character or ethical conduct is not the act done with the intention of obtaining the benefits of the materialistic-individualistic, even if done for love of neighbor or because of the beauty of an act or for beauty. Various concepts of character formation of the students has been defined in a number of scientific research results. Practical theory character management of learners to patterns that refers to the formation of character among students at the school are found. The importance of the role of educator and how hard it duties and responsibilities, especially the responsibility of the character for